2016
DOI: 10.1159/000444675
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis in Esophageal Eosinophilia Reveals Differential Galectin-3 Expression and S-Nitrosylation

Abstract: Background Aims: Esophageal eosinophilia (EE) can be caused by gastroesophageal reflux disease (GERD), proton-pump inhibitor-responsive EE (PPI-REE) or eosinophilic esophagitis (EoE). This study quantified protein expression and S-nitrosylation (SNO) post-translational modifications in EE to elucidate potential disease biomarkers. Methods: Proximal and distal esophageal (DE) biopsy proteins in patients with EE and in controls were assayed for protein content and fluorescence-labeled with and without ascorbate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…This cytokine array did, however, identify 6 cytokines/soluble factors whose expression was significantly upregulated in epithelium-enriched esophageal tissue of aged mice: bFGF, OPN, CRP, Lipocalin-2, NOV and Galectin-3. Among these, bFGF, OPN, and Galectin-3 have been shown to be upregulated in biospecimens from EoE patients with bFGF detected in plasma, OPN in urine, and Galectin-3 in esophageal biopsies (38)(39)(40). Although these factors have not been linked to EoE fibrosis, they have been associated with fibrosis in other tissue sites.…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine array did, however, identify 6 cytokines/soluble factors whose expression was significantly upregulated in epithelium-enriched esophageal tissue of aged mice: bFGF, OPN, CRP, Lipocalin-2, NOV and Galectin-3. Among these, bFGF, OPN, and Galectin-3 have been shown to be upregulated in biospecimens from EoE patients with bFGF detected in plasma, OPN in urine, and Galectin-3 in esophageal biopsies (38)(39)(40). Although these factors have not been linked to EoE fibrosis, they have been associated with fibrosis in other tissue sites.…”
Section: Discussionmentioning
confidence: 99%
“…All these observations further add to the functional repertoire of galectins since such interactions have been shown to contribute to, e.g., intracellular signaling and splicing [ 28 , 33 , 34 ]. Finally, it is noteworthy to point out that galectins can form heterodimers with family members as well as with cytokines [ 35 , 36 ] and that they can be subjected to both post-transcriptional and post-translational modifications [ 37 , 38 , 39 ], aspects of which we are only beginning to understand the functional consequences. Nevertheless, it is nowadays well established that galectins constitute a protein family with versatile functions that contributes to a plethora of molecular, cellular and biological processes.…”
Section: The Galectin Protein Familymentioning
confidence: 99%
“…The need for more research also applies to the role of post-translational modifications of galectins in endothelial cells. Different protein modifications with different functional effects on galectins have been reported, including proteolytic cleavage, phosphorylation, and S-nitrosylation [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. With regard to angiogenesis, it was shown that proteolytic processing of galectin-3 influences the angioregulatory activity of the protein (see also next section) [ 52 ].…”
Section: Endothelial Galectin Expressionmentioning
confidence: 99%